2019
DOI: 10.3389/fnins.2019.00556
|View full text |Cite
|
Sign up to set email alerts
|

A Crosstalk Between Brain Cholesterol Oxidation and Glucose Metabolism in Alzheimer’s Disease

Abstract: In Alzheimer’s disease (AD), both cholesterol and glucose dysmetabolism precede the onset of memory deficit and contribute to the disease’s progression. It is indeed now believed that oxidized cholesterol in the form of oxysterols and altered glucose uptake are the main triggers in AD affecting production and clearance of Aβ, and tau phosphorylation. However, only a few studies highlight the relationship between them, suggesting the importance of further extensive studies on this topic. Recently, a molecular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 88 publications
4
49
0
Order By: Relevance
“…Besides, cholesterol exerts an essential influence in plasma membrane regionalization, signal transduction, myelin sheath formation, and synaptic formation and maintenance (Chernick et al, 2019). Peripheral blood cholesterols can affect the human brain and AD through the blood-brain barrier (BBB) (Gamba et al, 2019). Our results showed that elevated TC levels were significantly associated with AD patients in later life.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Besides, cholesterol exerts an essential influence in plasma membrane regionalization, signal transduction, myelin sheath formation, and synaptic formation and maintenance (Chernick et al, 2019). Peripheral blood cholesterols can affect the human brain and AD through the blood-brain barrier (BBB) (Gamba et al, 2019). Our results showed that elevated TC levels were significantly associated with AD patients in later life.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, when cholesterol was lowered, the Precursor Protein of Aβ (APP) was swallowed into cells to decompose, which could reduce the extracellular presence of Aβ and the risk of AD (Martins et al, 2009). Furthermore, oxysterols (oxidative metabolites of cholesterols) may participate in AD progression via Liver X Receptors (LXR), which are key components in cholesterol homeostasis (Gamba et al, 2019;Merino-Serrais et al, 2019;Mouzat et al, 2019). For example, 24-hydroxycholesterol (24-OHC) can impede hyperphosphorylation of tau induced by deposition of Aβ in SK-N-BE cells by regulating the deacetylase sirtuin 1.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol synthesis and metabolism in the brain fully rely on de novo synthesis. The BBB, which prevents cholesterol uptake from the circulation, and the blood-cerebrospinal fluid (CSF) barrier (plasma is ultrafiltrated to be part of the CSF) are two natural barriers that prevent mixing of plasma and brain cholesterol (Gamba et al, 2019;Genaro-Mattos et al, 2019).…”
Section: Brain Cholesterol Metabolismmentioning
confidence: 99%
“…Here we present the discovery and validation of serum free oxysterol changes that distinguish cognitively normal participants from MCI patients. The de ned two-oxysterol penal features the most common side chain oxysterol of 27-hdroxycholesterol, which mainly derives from the peripheral circulation and ows into the brain [33], and its brain-derived end metabolite, 7α-hydroxy-3-oxo-4-cholestenoic acid, to which 27hdroxycholesterol is converted in the brain through enzymes of CYP27A1, CYP7B1 and HSD3B7 catalyzed oxidation, is then eliminated in the systemic circulation and in the CSF [12]. We also observed consistent and strong negative correlations between 7α-hydroxy-3-oxo-4-cholestenoic acid and global cognition, indicated by MoCA score, as well as processing speed performance, indicated by SDMT score.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the oxysterols resulting from cholesterol autoxidation potentially implicated in AD pathogenesis is now emerging. By crossing the BBB, they can also ow from the brain into the circulation and vice versa and have been identi ed to be signi cantly increased during AD progression [12]. Therefore, oxysterol pro les, rather than single compound, in biological uids and organs may be more useful as the biomarkers of diseases.…”
Section: Introductionmentioning
confidence: 99%